COMPARISON OF THE POE2WE MODEL'S EFFECTIVENESS WITH THE 5M SCIENTIFIC APPROACH TO PROBLEM-SOLVING ABILITY IN SIMPLE HARMONIC MOTION - Adam Malik; Sya’iidah Muntahaa Karmini; Rena Denya Agustina; Andi Rohendi Nugraha (EDUSAINS, 2022)
This study aims to determine the implementation of learning, improvement, and differences in problem-solving abilities among students who learn using the Prediction, Observation, Explanation, Elaboration, Writing, and Evaluation (POE2WE) models aided by PhET simulation and scientific approach aided by Amrita Olab Edu. The noneequivalent control group design was used in a quasi-experimental design. The sample consists of 31 students from classes X MIPA 2 and X MIPA 3 at one of Tasikmalaya's senior high schools. A student worksheet with SAS and a problem-solving ability test were used as instruments. The SAS sheet analysis results show that the average learning implementation in the experimental class is 78.9% in the effective category, while the control class is 75.9% in the effective category. Based on the N-gain, the experimental class improved students' problem-solving abilities by 0.73 in the high category, while the control class improved by 0.62 in the medium category. The t-test results revealed that the tcount (4.66) > ttable (2.00) and the sig. (2-tailed) 0.000018 indicate differences in the problem-solving abilities of students who learn using the POE2WE model and the scientific approach 5M on simple harmonic motion material. The POE2WE model can train and improve students' problem-solving abilities. How To Cite: Malik, A., Karmini, S.M., Agustina, R.D., Nugraha, R. (2022). Comparison of The POE2WE Model's Effectiveness with the 5M Scientific Approach to Problem-Solving Ability in Simple Harmonic Motion. EDUSAINS, 14 (2) : 126-136.